Exploiting Immiscible Aqueous-Nonaqueous Electrolyte Interface toward a Membraneless Redox-Flow Battery Concept. Issue 12 (1st January 2017) - Gong, Ke; Xu, Fei; Lehrich, Michael G.; Ma, Xiaoya; Gu, Shuang; Yan, Yushan
Abstract : A new concept of membraneless battery based on immiscible aqueous and nonaqueous stratified-electrolytes was studied in a static cell for the purpose of constructing a redox flow battery (RFB). By selectively dissolving the negative redox pair and the positive one in aqueous and nonaqueous electrolyte, respectively, two redox pairs are thermodynamically separated in their own phases without the need of membrane as separator. A zinc-ferrocene (Zn-Fc) static battery is demonstrated as an example, in which Zn 2+ /Zn in aqueous electrolyte and Fc + /Fc in nonaqueous electrolyte (butyl acetate) were used as the negative and positive redox pair. Electrochemical properties of Fc + /Fc in butyl acetate are studied and the performance of membraneless Zn-Fc battery is evaluated. The new design in this work can be potentially applied and upgraded to redox flow battery given the flowing capability of both electrolytes.